Islamic Money and Banking : Integrating Money in Capital Theory. - Toutounchian, Iraj (John Wiley & Sons, 2011)
This book examines how money, in the absence of interest (Riba) and money market can become an endogenous variable of an economic system. It further tries to integrate money in capital theory and to make monetary sector part of the real sector aiming at removing the problems that arise from separation of the two.